IMPLEMENTATION OF OBJECT TRACKING AND GIMBAL POINTING IN MULTIROTOR DRONE USING OPENTLD ALGORITHM ON ROS (ROBOT OPERATING SYSTEM) FRAMEWORK - Hariz Dzulfikar , Fadhel
Missile technology is part of Indonesia's defense and security industry development program. In missile technology, there is a main part that functions as the final guide towards the target of the missile system, that is Electro Optical Seeker (EOS) system that uses Computer Vision to perform digital image processing to track the target. In its development, we use UAV (Unmanned Aerial Vehicle), such as fixed wing UAV and UAV multirotor to model the actual missile system.